“There isn't anybody else like me around here”: the insider-outsider status of LGBT residents in housing with care schemes for older people - Willis, Paul; Beach, Brian; Powell, Jillian; Vickery, Alex; Cameron, Alisa; Smith, Randall (Frontiers in Sociology, 2023)
The intersections between aging, social minority status and housing needs in later life is a neglected area of sociological exploration, even more so for older people who identify as lesbian, gay, bisexual and trans (LGBT). Recent sociological findings indicate that older LGBT people in housing schemes stress the importance of bonding social capital and look to other people in their social networks who reflect their identities and experiences as sources of support. In this paper, we examine the insider-outsider status occupied by older LGBT residents living in housing schemes that provide some form of care and support, for example extra care and independent living schemes. We present qualitative findings generated from a mixed-methods study of social inclusion practices in housing with care in England and Wales (UK) (2019-22). In this study 15 LGBT residents participated in semi-structured interviews (55–79 years of age) across a total of 31 interviews. Through a queer gerontological lens we examine how older LGBT people are socially situated within mainstream housing schemes in which they experience partial visibility while also encountering exclusionary pressures that locate them as “the other.” This insider-outsider status undermines the premise of housing with care schemes to provide safe, secure spaces to grow old. We discuss three core themes: (1) how LGBT residents navigate their outsider status in scheme life and how the intersection of disability and minority status amplifies this social location; (2) the exclusionary practices exercised by other residents that reinforce boundaries of sexual and gender normalcy; and, (3) the heightened importance of maintaining external social connections among LGBT residents. We conclude by introducing an alternative notion of marginal aging and expanding on the implications for housing providers, reflecting on their responsibilities for promoting and maintaining queer-friendly environments.